LUDWIG WITTGENSTEIN: RELIGION AS A FORM OF LIFE - Voragen, Roy (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2008)
While Wittgenstein is not famous for his writings on religion, it iscertainly possible to interpret his work in such a way that it can beapplied to religion. As Wittgenstein's work is generally divided inearly and late work, this paper provides two interpretationregarding religion. His early work – Tractatus Logico-Philosophicus – can be considered a form of negative theology.His later work – Philosophical Investigations – offers ananthropologic method, i.e. the language game, that can be appliedto religion.